Evaluation of Practices of Cage Culture in Chandil Dam in Jharkhand, India - Jahan, Nuzhat; Srivastava, Pragya (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Jharkhand, one of the rich natural resources states of India, is endowed with vast fresh water resources in the form of tanks/ponds, reservoirs and dams. Dams in Jharkhand play important role in fish farming, irrigation, power generation and a wonderful tourist place. There are more than 84 dams in Jharkhand of which Chandil dam is one of the popular dams located in the Seraikela-Kharsawan district stands on the Subarnrekha River. This dam has a height of about 56.80 meters and a length of about 720.10 meters. Chandil dam has a catchment area of ​​1,963 square kilometres having a total of 90 cages. Each cage is equipped with 20 batteries to facilitate fish farming. Pangasius and Tilapia are the most preferred species for cage culture in Chandil dam. Each cage contains 4,500 specimens of these fish species. The fish are fed twice daily pellets containing 31% crude protein at 4-6% of their body weight. In 7-8 months, these fish reach a weight of about 1.2 kilogram. The average fish production per cage in the Chandil and its Sanaua dam basins is 4,000 kg. This high productivity contributes to the success of caging, which utilizes large bodies of water and meets the state’s growing demand for animal protein. The fisherman earns Rs.34432 from per cage. It was observed that the cage culture in dam is an excellent way to maximize production potential and make efficient use of large bodies of water. The present study was carried out in Chandil dam with the objective to assess the cage culture practices and fish production status. The assessment was done using the NFDB guidelines of cage culture in inland open water bodies of India using 15 parameters. Interviews with officials of Department of Fisheries and fishers was done to enquire if the guidelines were followed using a 3 point scale. This was corroborated by observation and field visits, so as to adopt the triangulation method.